APLIKASI SISTEM INFORMASI PENJUALAN APOTEK - Onny Purnamayudhia; Eko Budi Satoto (JURNAL TEKNIK INDUSTRI, 2014)
Business management in the field of pharmacy requires a Sales Information databasesystems. The purpose of this study is to design and apply the Sales Information System and toidentify the needs and requirements of the new system are made in order to improve the weaknessin the sales system. The method used is to make the sales information system design phases makesflow diagram and context diagram. The results of the study were achieved is to produce a draftSales Information System that can find solutions quickly and effectively than the existing systemwith a computerized system. Software used is by using Microsoft Visual Basic 6.